Surgical consent, perception of the patients who underwent a surgical operation in the Kurdistan region, Iraq - Dawan Jamal Hawezy (BMC Medical Ethics)
Abstract Introduction Patient satisfaction is a significant measure of healthcare service quality as the patient is the center of any surgical procedure. Patient satisfaction refers to the extent to which a patient’s expectations of optimal care align with their perception of the care received. Patient satisfaction during informed consent is enhanced when written informed consent is accompanied by verbal consent in the preoperative period. Satisfied patients are more inclined to adhere to therapy, engage actively in their care, utilize healthcare services, willingly partake in decision-making, and remain with a healthcare provider. This research examines the practical and ethical considerations of obtaining informed consent during surgical procedures. To better understand and make informed decisions, this study aims to assess the efficacy of present consent methods and pinpoint obstacles patients encounter. Methodology A cross-sectional study was conducted from April to December 2024. Data were gathered by second-year students from Koya University’s Faculty of General Medicine by interviewing postoperative patients who had undergone general surgical procedures. The results were entered into a Google form and analyzed using SPSS27. Results In interviews with participants, 430 out of 572 patients (75%) indicated trust in their surgeons performing the surgery, while 525 patients (91%) expressed respect for their surgeons’ opinions. However, 41% (239 patients) reported not reading the informed consent form, and a similar percentage denied that the details of the form were explained by the medical staff responsible for the surgery as there are some medical terms or situations in the form that are challenging to assume if not explained. Conclusion Compared to others, participants with a higher educational level sought extensive time from the responsible surgeons to discuss every detail of the surgery before signing the informed consent, with a statistically significant difference observed. A similar difference was noted between private and public hospitals.